2022
DOI: 10.3390/d14070563
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of Selected Kenyan Eucalyptus Species Inferred from MatK, rbcL and TrnL-F Genes and Their Suitability for Power Transmission Poles

Abstract: Genus Eucalyptus belongs to the family Myrtaceae and consists of more than 900 species, various hybrids and varieties. The major species that are grown in Kenya are Eucalyptus grandis, E. globulus, E. saligna and E. camaldulensis. Most Eucalyptus species are highly dependent on rainfall and this is challenged by climatic changes owing to global warming making it difficult to effectively match the availability of mature trees and the market demand especially for use as power transmission poles. With the widespr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, in general nucleotide composition T. sumatrana from Sumatra has a similarity with the sequence from GenBank. The GC content is higher than AT content, causing a more stable bond for this region (Borisova et al 1993;Chebet et al 2022) explain that the trnL-trnF region is a conservative region, where this region that has remained essentially unchanged throughout evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in general nucleotide composition T. sumatrana from Sumatra has a similarity with the sequence from GenBank. The GC content is higher than AT content, causing a more stable bond for this region (Borisova et al 1993;Chebet et al 2022) explain that the trnL-trnF region is a conservative region, where this region that has remained essentially unchanged throughout evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The trnL-trnF region is one of the recommended regions for DNA Barcode (Zanjanchi and Mehrvarz 2015;Sevindik et al 2019;Sanna et al 2019;Sevindik and Okan 2020;Yi et al 2021;Hocaoglu-Ozyigit et al 2022). The region has a conservative secondary structure and contains homologous elements throughout land plants, the sequence is catalytic, and this region can be used for evolutionary studies at higher taxonomic levels (Chebet et al 2022). The trnL-trnF gene is widely used since the 1990s (D'yachenko et al 2015;Hartvig et al 2015;Koohdar and Sheidai 2022;Kipkiror et al 2023), and has shown successful application in plant molecular systematics in flowering plants (Chen et al 2013), such as Mangifera spp.…”
Section: Introductionmentioning
confidence: 99%
“…E ucalypt (safeda) is evergreen, fastest growing multipurpose species (MPTs), widely adopted in various climatic conditions. It belongs to the Myrtaceae family, with three genera such as Eucalyptus, Corymbia and Angophora comprising about 900 species (Pereira et al, 2014;Mengistu et al, 2020;Chebet et al, 2022). More than 700 known eucalypt species are native to Australia (Hooga et al, 2019) and few species are indigenous to Indonesia, the Philippines and New Guinea (Stanturf et al, 2013;Hayat et al, 2015).…”
Section: Introductionmentioning
confidence: 99%